2017
DOI: 10.1093/schbul/sbw192
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and Extrastriatal Dopamine Transporter Availability in Schizophrenia and Its Clinical Correlates: A Voxel-Based and High-Resolution PET Study

Abstract: Neuroimaging studies investigating dopamine (DA) function widely support the hypothesis of presynaptic striatal DA hyperactivity in schizophrenia. However, published data on the striatal DA transporter (DAT) appear less consistent with this hypothesis, probably partly due to methodological limitations. Moreover, DAT in extrastriatal regions has been very poorly investigated in the context of schizophrenia. In order to address these issues, we used a high resolution positron emission tomograph and the selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Studies examining DAT density in the striatum have found no consistent differences between patients and controls, although, as with D2 receptors, variability is increased in schizophrenia, suggesting that differences may exist within a subgroup. A more recent study did find significantly raised striatal DAT levels in patients, but this was observed in those with a chronic illness with long‐term antipsychotic exposure.…”
Section: Dopaminementioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining DAT density in the striatum have found no consistent differences between patients and controls, although, as with D2 receptors, variability is increased in schizophrenia, suggesting that differences may exist within a subgroup. A more recent study did find significantly raised striatal DAT levels in patients, but this was observed in those with a chronic illness with long‐term antipsychotic exposure.…”
Section: Dopaminementioning
confidence: 99%
“…There have been fewer studies examining extra‐striatal regions, although the ones that have been undertaken do suggest that thalamic DAT levels may be raised in patients.…”
Section: Dopaminementioning
confidence: 99%
“…In this study, we used PET images acquired with [ 11 C]PE2I in healthy and psychiatric samples, on which previous PET studies investigating DAT were based (Leroy et al, 2012;Karila et al, 2016;Artiges et al, 2017). From this database, twenty-seven participants were selected based on the combined presence of PET images and fMRI data acquired with the MID task, that passed quality control (Supplementary Figure S1).…”
Section: Participantsmentioning
confidence: 99%
“…As previously described (Karila et al, 2016;Artiges et al, 2017), we used a mask for the PET statistical analysis, in order to include only main DA regions. It included basal ganglia, insula, amygdala, thalamus, midbrain, anterior cingulate gyrus, inferior frontal or right index finger to hit a target (white square) that appears for a short time on the left or right side of the screen.…”
Section: Pet Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation